Expression of full length fusion (F) protein gene of Newcastle disease virus in mammalian expression system - MANJUNATH, S; VIJAYARANI, K; KUMANAN, K (The Indian Journal of Animal Sciences, 2014)
The present study was carried out to clone and express fusion protein gene of Newcastle disease virus in mammalian expression system. The Newcastle disease virus (2K3) isolate from pigeon was propagated in 9–11 day-old embryonated chicken eggs and infected allantoic fluid was collected for RNA isolation. The fusion (F) gene of 1.68 Kb was amplified with cDNA as template and was cloned in TOPO cloning vector. The recombinant TOPO colonies were digested with NcoI and XhoI enzymes, the insert released was further ligated into pTriEx Neo 1.1 expression vector digested with the same enzymes and was transformed in Escherichia coli. The recombinant pTriEx colonies confirmed by colony PCR and restriction digestion were induced with 1mM IPTG which showed expressed fusion protein of 55 kDa at 4 h post induction and increased in overnight induced cultures. The recombinant pTriEx plasmid was transfected into vero cells. The cell lysate collected at 48 h and 72 h post transfection showed expressed fusion protein with the molecular weight of 55 kDa in 12% SDS-PAGE. The protein was further confirmed to be NDV specific by its immunoreactivity with NDV antiserum raised in rabbits showing fusion protein of 55 kDa. The immunofluorescence assay of transfected vero cells exhibited a bright cytoplasmic fluorescence confirming the fusion protein expression.